Residual stresses at weld repairs and effects of repair geometry. (19th May 2017) - Song, S.; Dong, P.
ABSTRACT: In this study, an in-depth investigation of repair weld geometry effects on residual stress distributions in terms of both through-thickness membrane and bending content as well as its contribution to fracture driving force is carried out. Some major findings are: A fundamental difference in residual stress distributions between initial and repair welds can be characterised as a significant elevation of membrane and bending content in transverse residual stresses. The dominance of repair-induced residual stresses over those generated by initial welds suggests that initial weld residual stresses can be assumed negligible in repair weld modelling. A weld repair should be designed as long as possible, as narrow as possible and as shallow as possible.